2022
DOI: 10.12998/wjcc.v10.i9.2751
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in traumatic brain injury intensive care unit patients

Abstract: BACKGROUND The exact definition of Acute kidney injury (AKI) for patients with traumatic brain injury (TBI) is unknown. AIM To compare the power of the “Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease” (RIFLE), Acute Kidney Injury Network (AKIN), Creatinine kinetics (CK), and Kidney Disease Improving Global Outcomes (KDIGO) to determine AKI incidence/stage and their association with the in-hospital mortality rate of patients with TBI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…While insights into AKI incidence among neurocritical patients mainly stem from retrospective studies in single centers and exclude cases diagnosed with AKI upon admission, a recent study in a mixed neurological/neurosurgical ICU reported an overall AKI occurrence of 23.5% utilizing the SCr/UOP KDIGO criteria [ 9 ]. Interestingly, similar AKI rates were noted among specific brain pathologies, including TBI, 11.9–26.7% (KDIGO, SCr only) [ 10 – 14 ] and 17.7% (SCr/UOP KDIGO) [ 15 ]; acute stroke, 20.9–43.3% (KDIGO, SCr only) [ 16 , 17 ]; non-traumatic aneurysmal SAH, 16.7–23.7% (KDIGO, SCr only) [ 18 , 19 ], and ICH, 20.0–29.9% [ 18 , 20 22 ]. The few studies assessing RRT in patients with ABI reported overall rates of 0.3–5.6% among neurocritical patients [ 17 , 23 ].…”
Section: Aki Epidemiology and Outcomes In Neurocritical Carementioning
confidence: 72%
“…While insights into AKI incidence among neurocritical patients mainly stem from retrospective studies in single centers and exclude cases diagnosed with AKI upon admission, a recent study in a mixed neurological/neurosurgical ICU reported an overall AKI occurrence of 23.5% utilizing the SCr/UOP KDIGO criteria [ 9 ]. Interestingly, similar AKI rates were noted among specific brain pathologies, including TBI, 11.9–26.7% (KDIGO, SCr only) [ 10 – 14 ] and 17.7% (SCr/UOP KDIGO) [ 15 ]; acute stroke, 20.9–43.3% (KDIGO, SCr only) [ 16 , 17 ]; non-traumatic aneurysmal SAH, 16.7–23.7% (KDIGO, SCr only) [ 18 , 19 ], and ICH, 20.0–29.9% [ 18 , 20 22 ]. The few studies assessing RRT in patients with ABI reported overall rates of 0.3–5.6% among neurocritical patients [ 17 , 23 ].…”
Section: Aki Epidemiology and Outcomes In Neurocritical Carementioning
confidence: 72%